2021
DOI: 10.3390/en14185952
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal—Flow Processes and Flow Pattern in a Pulsating Heat Pipe—Numerical Modelling and Experimental Validation

Abstract: The aim of the article is to numerically model a two-dimensional multiphase flow based on the volume of fluid method (VOF) in a pulsating heat pipe (PHP). The current state of knowledge regarding the modeling of these devices was studied and summarised. The proposed model is developed within open source software, OpenFOAM, based on the predefined solver called interPhaseChangeFoam. The analyses were carried out in terms of the influence of four different mass transfer models between the phases, proposed by Tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Four sweep mesh models were analyzed to determine the appropriate mesh size for the CFD analysis. In particular, the current CFD simulation is a three-dimensional structure that is different from the two-dimensional modeling of previous research in the literature [45][46][47][48][49][50][51]. Moreover, Song et al [52] reported the importance of 3D simulation to reach accuracy and to see multidimensional flow behavior.…”
Section: Mesh Sensitivity Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…Four sweep mesh models were analyzed to determine the appropriate mesh size for the CFD analysis. In particular, the current CFD simulation is a three-dimensional structure that is different from the two-dimensional modeling of previous research in the literature [45][46][47][48][49][50][51]. Moreover, Song et al [52] reported the importance of 3D simulation to reach accuracy and to see multidimensional flow behavior.…”
Section: Mesh Sensitivity Analysismentioning
confidence: 95%
“…Several heat pipes [45][46][47][48][49][50][51][52] were subjected to numerical analysis. The volume of fluid (VOF) methodology, which is one of the most well-known methods, was used in their computational fluid dynamics to simulate the two-phase flow of liquid-vapor phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The article [7] titled "The Thermal-Flow Processes and Flow Pattern in a Pulsating Heat Pipe-Numerical Modelling and Experimental Validation" deals with very challenging and important problems related to multi-phase flows. Additionally, the authors present very interesting and original experiment of a flow in pulsating heat pipe.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%
“…Blasiak et al [23] studied a pulsating heat pipe using 2-D multiphase simulation. For this simulation, the VOF (volume of fluid) model was adopted, and the analysis was carried out with various mass transfer models between phases.…”
Section: Introductionmentioning
confidence: 99%